IMMUNE THROMBOCYTOPENIC PURPURA INDUCED BY VARICELLA ZOSTER IN AN 8-YEAR-OLD GIRL: A CASE REPORT - Praditina, Wening Gelar; Hapsari, Ariadne Tiara; Syamsu Hidayat, Muhammad Zaenuri; Bunga, Bunga; Tamia, Afra Bryges (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Varicella Zoster Virus (VZV) can trigger various complications, one of which is Immune Thrombocytopenic Purpura (ITP), although this occurrence is rare. ITP is a bleeding disorder caused by excessive platelet destruction due to autoantibodies. This case report presents an 8-year-old female child who developed varicella accompanied by severe thrombocytopenia. Initially, the patient experienced prodromal symptoms including fever, followed by the appearance of vesicular skin lesions that spread centrifugally. Laboratory tests revealed thrombocytopenia, supporting the diagnosis of ITP. The management included antiviral therapy with acyclovir, platelet transfusion, and corticosteroid therapy to reduce inflammation. Although ITP triggered by varicella is rare, prompt and appropriate management is essential to prevent life-threatening complications.